Persistent exploitation with intertemporal reproducible solution in pre-industrial economies - Weikai Chen; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2019)
This paper presents an intertemporal model of pre-industrial economies defined with leisure preference to study the condition of the emergence and persistence of exploitation as unequal exchange of labor. We show that pure workers are exploited in any finite periods if there is positive real profit rate, even though labor allocation among agents tends to be equalized in the limit regardless of the saving behaviors. The so-called Fundamental Marxian Theorem and Profit-Exploitation Correspondence Principle are generalized in the intertemporal setting with exploitation in the whole life, and the Class-Exploitation Correspondence Principle is established with exploitation within period.
Keywords: D51; D63; C61; B51; 330; Exploitation; Unequal Exchange of Labor; Persistence; Asymptotically Egalitarian